Ferroelectric Hf0.5Zr0.5O2 films on SrTiO3(111). Issue 21 (18th May 2022) - Song, Tingfeng; Estandía, Saúl; Dix, Nico; Gàzquez, Jaume; Gich, Martí; Fina, Ignasi; Sánchez, Florencio
Abstract : The orthorhombic phase of Hf0.5 Zr0.5 O2 is stabilized by tilted epitaxy on LSMO/SrTiO3 (111). The films present crystal variants with the polarization vector at different tilting angles with respect to the normal. Abstract : Ferroelectric HfO2 epitaxial films are of interest for determining intrinsic properties and for prototyping devices. Epitaxial (111)-oriented orthorhombic Hf0.5 Zr0.5 O2 films grown on La0.67 Sr0.33 MnO3 /SrTiO3 (001) are already being actively investigated. Presently, we have explored the use of SrTiO3 (111) substrates. We show that the orthorhombic phase is stabilized by tilted epitaxy, and the orientation of orthorhombic crystallites is different from that of equivalent films on SrTiO3 (001). The measured remanent polarization of above 14 μC cm −2 agrees well with the expected value considering the crystal orientation, the fraction of the ferroelectric phase in the film, and the predicted polarization for ferroelectric HfO2 . High endurance and retention are also measured.